OPTIMIZATION OF THE MATHEMATICAL MODEL OF THE GRADUATE EMPLOYMENT SYSTEM IN THE CONDITIONS OF THE DIGITAL ECONOMY (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the article, the creation of a mathematical model to optimize the selection of vacancies for graduates in enterprises. A graphic model of the percentage of skills and grades acquired by graduates of higher education institutions in mastering subjects based on the curriculum was created using the semantic method.
Keywords: Employment, skill, semantic graph, evaluation, optimization, graduate, mathematical model.